Shielding Property of Closed-Cell AlSi7 Foams and AlSi7 Bulk Materials against Gamma Rays - Uzun, Arif; Gökmen, Uğur; Çi̇ni̇ci̇, Hanifi; Kurnaz, Aslı; Çeti̇ner, Mehmet Atıf (Afyon Kocatepe Universitesi Fen Ve Muhendislik Bilimleri Dergisi, 2016)
The aim of this paper is experimental comparison of shielding properties against gamma rays among closed-cell AlSi7 foams and bulk materials. These materials were produced by powder metallurgy method. Gamma rays attenuation measurements were performed at photon energies of 88, 511, 662, 1173, 1275 and 1332.5 keV. The obtained results revealed that AlSi7 bulk materials offer better gamma rays attenuation capabilities due to their high density compared to closed-cell AlSi7 foams.
Keywords: Al foam; Gamma Ray; Shielding; Al foam; Gamma ray; Shielding; Attenuation coefficient.; Attenuation Coefficient; 13. Climate action; 7. Clean energy; 3. Good health